Estrategias de la Conciencia Fonológica para desarrollar la Lecto - Escritura en los niños y niñas de cuarto grado de Educación Básica de la escuela “Leandro Chuquimarca Daquilema” de la comunidad de San Juan de los Tipines, Parroquia Palmira, Cantón Guamote, Provincia de Chimborazo, período lectivo 2014-2015 - Cevallos Brito, Norma Patricia (2016)
The present study entitled “Phonological Strategies to develop Reading and Writing skills in fourth year students at the “Leandro Chuquimarca Daquilema” school, in a parish called San Juan de los Tipines - Palmira located in Guamote, province of Chimborazo, during the term 2014-2015. The study was conducted in order to develop phonological awareness when reading and writing, considering that phonology implies the acquisition and manipulation of sounds in a particular language related to the systematic exposition to acquire reading and writing skills, abilities that can be tested through cognitive and specific tasks that demand phonetic analytical and synthetic capabilities with a distinct level of complexity. As regards the methodology applied, they constituted the major support for this study, allowing us the application of the observation checklist aimed at the students that showed the data through graphics in order to perform the corresponding analysis and interpretation of information. Furthermore, this study constitutes a pedagogical tool to educators as it will permit them to find out different perspectives on a variety of experts on phonological awareness to improve education. In sum, the “Leandro Chuquimarca Daquilema’’ school will prioritize the importance to develop new phonological strategies in benefit of its students